Medical magnesium-based guided bone regeneration membrane as well as preparation method and application thereof

By generating a nano-scale hydroxyapatite composite coating on the surface of the pure magnesium matrix in situ, the problems of excessive degradation speed and poor bone formation and antibacterial performance of the magnesium-based GBR membrane are solved, and the corrosion resistance, antibacterial and bone-promoting effects of the magnesium-based GBR membrane are achieved, improving bone increment and implant safety.

CN119868666APending Publication Date: 2025-04-25SHANGHAI XUHUI DISTRICT DENTAL HOSPITAL (SHANGHAI XUHUI DISTRICT DENTAL DISEASE CONTROL & PREVENTION INSTITUTE) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411624981.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing medical pure magnesium materials, as GBR membrane materials, have too fast degradation speed and poor osteogenic and antibacterial properties, which may lead to insignificant postoperative inflammation, infection and bone increment effects.

Method used

In situ on the surface of the pure magnesium matrix, nano-scale hydroxyapatite coatings or nano-scale hydroxyapatite composite coatings, specifically including nano-hydroxyapatite composite quercetin, gallium ionic or gallium polyphenol coatings.

Benefits of technology

It significantly reduces the degradation rate of magnesium-based GBR membrane, improves its corrosion resistance, antibacterial properties and osteogenic differentiation ability, enhances the expression of alkaline phosphatase in bone marrow mesenchymal stem cells, promotes the migration of umbilical vein endothelial cells, improves the bone increment effect after implantation, and prevents infection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868666A_ABST
    Figure CN119868666A_ABST
Patent Text Reader

Abstract

The invention discloses a medical magnesium-based guided bone regeneration membrane as well as a preparation method and application thereof, and the medical magnesium-based guided bone regeneration membrane comprises a pure magnesium matrix and a nano-scale hydroxyapatite coating or a nano-scale hydroxyapatite composite coating generated on the surface of the pure magnesium matrix in situ. The nano-scale hydroxyapatite composite coating is a nano-hydroxyapatite composite quercetin coating, a nano-hydroxyapatite composite gallium ion coating or a nano-hydroxyapatite composite gallium polyphenol coating. The medical magnesium-based guided bone regeneration membrane disclosed by the invention has excellent corrosion resistance and in-vivo antibacterial effect; in addition, due to continuous release of magnesium ions, gallium ions and quercetin, osteoblast proliferation and stem cell differentiation can be effectively promoted. The magnesium-based guided bone regeneration membrane provided by the invention has good osteogenesis promoting capability, and can be widely applied to development of guided bone regeneration basement membrane materials and improvement of bone increment effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical materials, and in particular to a medical magnesium-based guided bone regeneration membrane and a preparation method and application thereof. Background Art

[0002] Insufficient alveolar bone often poses a challenge to oral implant restoration, and guided bone regeneration (GBR) technology is an effective treatment method suitable for horizontal or vertical bone augmentation. In this technology, the GBR membrane plays a vital role. It can effectively isolate rapidly proliferating epithelial cells and connective tissue, provide a relatively closed bone tissue growth environment, maximize the proliferation and differentiation of cells with regenerative ability in the bone defect area, and promote the formation of new bone.

[0003] The ideal GBR membrane material must have good biocompatibility to ensure that it is not rejected by the human body and is harmless to the human body. At the same time, it should also have excellent mechanical properties, such as an elastic modulus similar to that of bone tissue, excellent corrosion resistance and fatigue resistance.

[0004] At present, GBR membranes are mainly divided into two categories: non-degradable membranes (such as polytetrafluoroethylene, titanium mesh, etc.) and degradable membranes (such as collagen, magnesium alloy, zinc alloy, etc.). Non-degradable membranes require a second operation to remove and may increase the risk of wound infection; although degradable collagen membranes are biocompatible, their mechanical properties are poor and it is difficult to provide sufficient support. Although polylactic acid materials are degradable, the acidic environment generated during their degradation process may cause inflammation. In contrast, degradable metal materials have both excellent mechanical properties and low-toxic degradation products.

[0005] As a highly ductile metal material, degradable magnesium has an elastic modulus of about 35GPa, a tensile strength between 165-205MPa, a yield strength of 0.2MPa, and good degradation performance. The degradation product magnesium ions are essential to the human body. Compared with degradable materials such as polylactic acid and polylactic acid glycolic acid, magnesium metal film has better biocompatibility and mechanical properties closer to human bones.

[0006] Although degradable magnesium metal materials have been used in bone nails, bone plates, degradable closure clips and other fields, there are still some problems in practical applications. The degradation rate of pure magnesium is too fast, resulting in a sharp increase in local pH, a decrease in mechanical function and difficulty in cell adhesion. These factors limit the development of magnesium metal medical materials. In addition, magnesium metal does not significantly promote bone regeneration. At the same time, the antibacterial effect of the magnesium metal surface is not ideal. Bacteria can easily colonize on its surface, leading to implant failure. Therefore, surface modification of magnesium metal to improve its osteogenic and antibacterial properties is of great significance for promoting the clinical application of magnesium-based GBR membranes. Summary of the invention

[0007] In order to solve the problems that the existing medical pure magnesium materials used as GBR membrane materials have too fast degradation rate, poor osteogenesis and antibacterial properties, which may lead to postoperative inflammation, infection and insignificant bone augmentation effect, the present invention provides a magnesium-based guided bone regeneration membrane with antibacterial, osteogenesis and corrosion resistance, and a preparation method and application thereof.

[0008] A medical magnesium-based guided bone regeneration membrane comprises a pure magnesium matrix and a nano-scale hydroxyapatite coating or a nano-scale hydroxyapatite composite coating generated in situ on the surface of the pure magnesium matrix.

[0009] Furthermore, the nano-hydroxyapatite composite coating is a nano-hydroxyapatite composite quercetin coating, a nano-hydroxyapatite composite gallium ion coating or a nano-hydroxyapatite composite gallium polyphenol coating.

[0010] A method for preparing a medical magnesium-based guided bone regeneration membrane comprises the following steps:

[0011] (1) pre-treating the magnesium ingot into a pure magnesium square sheet as a pure magnesium matrix, and performing a grinding process;

[0012] (2) In situ construction of nano-hydroxyapatite coating, nano-hydroxyapatite composite quercetin coating, nano-hydroxyapatite composite gallium ion coating or nano-hydroxyapatite composite gallium polyphenol coating on the surface of pure magnesium substrate by hydrothermal method;

[0013] Furthermore, the step (1) is to grind a pure magnesium ingot of 10 mm×10 mm×0.2 mm in size using 400 mesh and 1000 mesh silicon carbide sandpaper in turn, and then use alcohol ultrasonic cleaning twice, each time for 3-10 minutes to obtain a pure magnesium matrix, which is then stored in alcohol and taken out and dried before use.

[0014] Furthermore, in the step (2), the in-situ construction of the nano-hydroxyapatite coating is performed by placing the pure magnesium substrate treated in the step (1) in a hydrothermal reactor containing a tetrafluoroethylene liner, adding a precursor solution containing 0.05 M calcium ethylenediaminetetraacetate and 0.05 M potassium dihydrogen phosphate at a pH of 9, and placing the substrate in an oven at 80-100° C. for treatment for 20-28 hours.

[0015] Furthermore, the step (2) of in-situ construction of the nano-hydroxyapatite composite quercetin coating is to place the magnesium sheet treated in the step (1) in a hydrothermal autoclave containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at a pH of 9, add 0.4-0.6g / L quercetin, and place in an oven at 80-100°C for treatment for 20-28h.

[0016] Furthermore, the step (2) of in-situ construction of the nano-hydroxyapatite composite gallium ion coating is to place the magnesium sheet treated in the step (1) in a hydrothermal kettle containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at a pH of 9, add 0.8-1.2g / L gallium nitrate, and place in an oven at 80-100°C for treatment for 20-28h.

[0017] Furthermore, the step (2) of in-situ construction of the nano-hydroxyapatite composite gallium polyphenol coating is to place the magnesium sheet treated in the step (1) in a hydrothermal autoclave containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at a pH of 9, add 0.4-0.6g / L quercetin and 0.8-1.2g / L gallium nitrate, and place in an oven at 80-100°C for treatment for 20-28h.

[0018] A medical magnesium-based guided bone regeneration membrane is used in the preparation of a guided bone regeneration membrane aimed at promoting osteogenesis in bone augmentation surgery.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1) The degradation rate of the magnesium-based GBR membrane modified by the method of the present invention is significantly reduced, and after electrochemical testing, it is proved to have good corrosion resistance;

[0021] 2) The method for preparing the surface-modified nano-hydroxyapatite composite gallium polyphenol coating of the magnesium-based GBR membrane of the present invention has the advantages of simple process and easy-to-control preparation conditions;

[0022] 3) The magnesium-based GBR membrane surface modified coating of the present invention significantly promotes the expression of alkaline phosphatase in rat bone marrow mesenchymal stem cells, thereby facilitating osteogenic differentiation;

[0023] 4) The magnesium-based GBR membrane surface modified coating of the present invention has good antibacterial effect both in vivo and in vitro;

[0024] 5) The magnesium-based GBR membrane surface modified coating described in the present invention exhibits an excellent ability to promote the migration of umbilical vein endothelial cells, thereby facilitating the repair and healing of soft tissues. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the SEM high-resolution spectrum of the samples prepared in Examples 1-5, where Figure 1 a is untreated pure magnesium flakes, Figure 1 b is the HA sample obtained in Example 2, Figure 1 c is the HAQ sample obtained in Example 3, Figure 1 d is the HAGa sample obtained in Example 4, sample Figure 1 e is the HAGaQ sample obtained in Example 5. The surface of the sample prepared in Example 1 is smooth and has no specific structure; the surface of the samples prepared in Examples 2 to 3 shows an island-like growth coating morphology; the surface of the samples prepared in Examples 4 to 5 is composed of dense, small-sized nanoparticles, forming a dense coating.

[0026] Figure 2 a is the EIS curve obtained by testing the materials prepared in Examples 1-5, Figure 2 b is Figure 2 A partial enlarged view of a. Figure 2 c is the dynamic polarization potential diagram of the sample. The results show that after surface modification, the surface corrosion resistance of the magnesium-based material is significantly improved, and the HAGaQ sample has the strongest corrosion resistance.

[0027] Figure 3 The XRD curves of the samples prepared in Examples 1 to 5 are shown in Table 1. Compared with Example 1, the samples obtained in Examples 2 to 5 have the peak position of hydroxyapatite, indicating that a hydroxyapatite coating is formed on the surface of the magnesium-based metal after the modification treatment;

[0028] Figure 4 Figure 2 shows the FT-IR curves of quercetin and HAGaQ samples. The results show that quercetin is successfully loaded on the surface and successfully coordinated with metal ions to form a stable coating.

[0029] Figure 5 The cell proliferation activity of rat bone marrow mesenchymal stem cells cultured on the surface of the samples prepared in Examples 1-5 was tested. The results showed that the pure magnesium film was cytotoxic, while the magnesium-based metal film modified by the coating had reduced cytotoxicity and good biocompatibility, and the HAGaQ sample had the best cytocompatibility.

[0030] Figure 6 Cell viability of human umbilical vein endothelial cells cultured on the sample surface prepared for Example 1-5 ( Figure 6 a) and the migration capacity of human umbilical vein endothelial cells cultured after the sample extract was diluted one-fold ( Figure 6 b, Figure 6 c) The results showed that pure magnesium film was cytotoxic, while the cytotoxicity of magnesium-based metal film modified by coating was reduced, especially HAQ, HAGa and HAGaQ group samples had good biocompatibility. The cell migration results showed that in the 24h co-culture environment, the extract of HAGaQ group could significantly promote the migration of human umbilical vein endothelial cells.

[0031] Figure 7The expression of alkaline phosphatase (ALP) of rat bone marrow mesenchymal stem cells cultured on the surface of the samples prepared in Examples 1-5. The results show that the samples prepared in Examples 3-5 have significantly improved ability to stimulate stem cell ALP expression compared with the samples prepared in Examples 1-2, especially the HAGaQ group samples have the best effect of promoting ALP expression, indicating that they have a better effect of promoting osteogenic differentiation.

[0032] Figure 8 The antibacterial plating results of the samples prepared in Examples 1 to 5. The plating results of Staphylococcus aureus in vitro under PBS environment showed that both the pure magnesium group and the HAGaQ group samples had excellent antibacterial effects.

[0033] Fig. 9 The antibacterial plating results of the samples prepared for Examples 1 to 5 in vivo were shown in Figure 1. The plating results of Staphylococcus aureus in vivo and the Giemsa staining results showed that the HAGaQ group samples also had a good antibacterial effect in vivo. DETAILED DESCRIPTION

[0034] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0035] The present invention relates to a magnesium-based guided bone regeneration membrane with antibacterial, osteogenesis and corrosion resistance properties. The present invention uses medical metal magnesium as a substrate and uses hydrothermal technology to in-situ construct a nano-hydroxyapatite coating or a nano-hydroxyapatite composite coating on its surface. The nano-hydroxyapatite composite coating is a nano-hydroxyapatite composite quercetin coating, a nano-hydroxyapatite composite gallium ion coating or a nano-hydroxyapatite composite gallium polyphenol coating. The coating can improve the corrosion resistance of metal magnesium, reduce the degradation and hydrogen production rate, and improve its biocompatibility. It can also significantly improve the antibacterial, angiogenic and osteogenesis properties of the magnesium membrane, thereby facilitating the improvement of the bone augmentation effect after the magnesium membrane is implanted and effectively preventing infection.

[0036] The method for preparing the medical magnesium-based guided bone regeneration membrane comprises the following steps:

[0037] (1) Pre-treating a magnesium ingot into a pure magnesium square sheet as a pure magnesium matrix, and polishing a pure magnesium ingot of 10 mm × 10 mm × 0.2 mm using 400 mesh and 1000 mesh silicon carbide sandpaper in turn, followed by ultrasonic cleaning with alcohol twice, each time for 3-10 min to obtain a pure magnesium matrix, which is then stored in alcohol and taken out to dry before use;

[0038] (2) In situ construction of a nano-hydroxyapatite coating, a nano-hydroxyapatite composite quercetin coating, a nano-hydroxyapatite composite gallium ion coating or a nano-hydroxyapatite composite gallium polyphenol coating on the surface of a pure magnesium substrate by a hydrothermal method; wherein:

[0039] The in-situ construction of the nano-hydroxyapatite coating is to place the pure magnesium substrate treated in step (1) in a hydrothermal reactor containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at pH = 9, and place it in an oven at 80-100° C. for 20-28 hours;

[0040] The in-situ construction of the nano-hydroxyapatite composite quercetin coating is to place the magnesium sheet treated in step (1) in a hydrothermal reactor containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at pH = 9, add 0.4-0.6g / L quercetin, and place in an oven at 80-100°C for 20-28h;

[0041] The in-situ construction of the nano-hydroxyapatite composite gallium ion coating is to place the magnesium sheet treated in step (1) in a hydrothermal reactor containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at pH = 9, and add 0.8-1.2g / L gallium nitrate, and place in an oven at 80-100°C for 20-28h;

[0042] The in-situ construction of the nano-hydroxyapatite composite gallium polyphenol coating is to place the magnesium sheet treated in step (1) in a hydrothermal autoclave containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at a pH of 9, add 0.4-0.6g / L quercetin and 0.8-1.2g / L gallium nitrate, and place in an oven at 80-100°C for treatment for 20-28h.

[0043] The following further exemplifies the present invention in detail. It should be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of the present invention. The specific process parameters of the following examples are only examples in a suitable range, and those skilled in the art can make selections within a suitable range through the description of this article, but are not limited to the specific numerical values ​​​​exemplified below. Unless otherwise defined or specified, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equal to the recorded content can be applied to the method of the present invention.

[0044] Example 1

[0045] Pure magnesium GBR membrane: A magnesium ingot containing 99.98% magnesium is pretreated into a pure magnesium square sheet with a thickness of 0.2 mm and a side length of 10 mm. Then, the pure magnesium sheet with a specification of 10 mm × 10 mm × 0.2 mm is polished using 400 mesh and 1000 mesh silicon carbide sandpaper, and then ultrasonically cleaned with alcohol twice, each time for 5 minutes, and then stored in alcohol and taken out to dry before use.

[0046] Example 2

[0047] HA GBR membrane: The magnesium sheet treated in Example 1 was placed in a hydrothermal kettle lined with tetrafluoroethylene, a precursor solution containing 0.05 M calcium ethylenediaminetetraacetate and 0.05 M potassium dihydrogen phosphate at pH = 9 was added, and the membrane was placed in an oven at 80°C for 20 hours. The obtained sample was named HA.

[0048] Example 3

[0049] HAQ GBR membrane: The magnesium sheet treated in Example 1 was placed in a hydrothermal autoclave lined with tetrafluoroethylene, and a precursor solution containing 0.05 M calcium ethylenediaminetetraacetate and 0.05 M potassium dihydrogen phosphate at pH = 9 was added, and 0.5 g / L quercetin was added. The sample was placed in an oven at 90°C and treated for 24 hours. The obtained sample was named HAQ.

[0050] Example 4

[0051] HAGa GBR membrane: The magnesium sheet treated in Example 1 was placed in a hydrothermal reactor lined with tetrafluoroethylene, and a precursor solution containing 0.05 M calcium ethylenediaminetetraacetate and 0.05 M potassium dihydrogen phosphate at pH = 9 was added, and 1.0 g / L gallium nitrate (Ga(NO 3 ) 3 9H 2 O), placed in an oven at 100°C for 24 h, and the obtained sample was named HAGa.

[0052] Example 5

[0053] HAGaQ GBR membrane: The magnesium sheet treated in Example 1 was placed in a hydrothermal reactor lined with tetrafluoroethylene, and a precursor solution containing 0.05 M calcium ethylenediaminetetraacetate and 0.05 M potassium dihydrogen phosphate at pH = 9 was added, and 1.0 g / L gallium nitrate (Ga(NO 3 ) 3 9H 2 O), placed in a 90°C oven for 24 h, and the obtained sample was named HAGaQ.

[0054] Example 6

[0055] The samples obtained in the above examples 1-5 were subjected to SEM testing. Figure 1As shown, the surface of pure magnesium is smooth and flat, while the surfaces of HA, HAQ, HAGa and HAGaQ samples have granular deposition structures.

[0056] Example 7

[0057] The samples obtained in Examples 1-5 were subjected to electrochemical tests. When each sample was tested, the contact area was 0.25 cm 2 During the dynamic potential test, the voltage range was -1V to +1V and the scanning speed was 0.01V / s. The data obtained are as follows Figure 2 As shown. Compared with pure magnesium film, the impedance arcs of HA, HAQ, HAGa and HAGaQ samples all show an increasing trend, and their dynamic polarization potential curves also shift in the direction of decreasing corrosion current density. This shows that after the corresponding treatment, the coating formed on the surface of the magnesium film significantly improves its corrosion resistance, and among these coatings, the corrosion resistance of the HAGaQ film is the most outstanding.

[0058] Example 8

[0059] The samples obtained in the above examples 1-5 were subjected to XRD test. The test conditions were: voltage 30 kV, scanning angle range 5° to 80°, scanning speed 4° / min. Figure 3 As shown, hydroxyapatite coatings were successfully formed on the surfaces of HA, HAQ, HAGa and HAGaQ samples.

[0060] Example 9

[0061] The sample obtained in Example 5 and quercetin were subjected to FT-IR testing. Figure 4 As shown, the vibration peaks of the C=O bond (carbonyl group) and the phenolic hydroxyl group observed in the test results clearly indicate that the coating of the HAGaQ sample contains quercetin components.

[0062] Example 10

[0063] The samples obtained in the above examples 1-5 were subjected to a rat bone marrow mesenchymal stem cell activity test, and the specific steps were as follows:

[0064] The samples were sterilized with 75% alcohol and placed in a 24-well plate. 5 × 10 4 cell / well stem cells and 1 mL of La-MEM complete medium, changing the medium every two days, and detecting cytotoxicity with alamarBlue, e.g. Figure 5 As shown, pure magnesium film has obvious cytotoxicity, while HA, HAQ, HAGa and HAGaQ sample coatings can significantly reduce the cytotoxicity of pure magnesium film, and the cell viability on the surface of HAGaQ sample is the strongest.

[0065] Embodiment 11

[0066] The samples obtained in the above Examples 1-5 were subjected to the human umbilical vein endothelial cell migration test, and the specific steps were as follows:

[0067] 1) Place the sample sterilized with 75% alcohol in a 5 mL centrifuge tube and add 1.6 mL of DMEM complete medium; extract at 37°C for 72 hours. Obtain 100% extract for later use.

[0068] 2) Take a 24-well plate, stick a non-toxic sterilization tape with a width of 1 mm on the bottom of the plate, and then place the 24-well plate with the tape under ultraviolet light for sterilization overnight.

[0069] 3) 5×10 human umbilical vein endothelial cells were seeded in each well of a 24-well plate. 4 cell / mL.

[0070] 4) Place the cell culture plate in a 37°C, 5% CO 2 , incubate in a cell culture incubator with saturated humidity; after culturing for 1 day, remove the tape, make a scratch with a width of 1 mm, and replace the culture medium with 50% extract.

[0071] 5) Take photos after 24 hours of cultivation.

[0072] 6) Use image J software to count the migration area and calculate the migration rate, such as Figure 6 As shown, the 50% extract of the HAGaQ sample obtained in Example 5 can significantly promote the migration of human umbilical vein endothelial cells.

[0073] Example 12

[0074] The samples obtained in the above examples 1-5 were subjected to a human umbilical vein endothelial cell viability test, and the specific steps were as follows:

[0075] 1) Place the sterilized sample in a 24-well plate. Inoculate 5×10 4 cell / mL human umbilical vein endothelial cells 1mL.

[0076] 2) After one day of culture, the samples were transferred to a new 24-well plate, and the medium was changed every 2 days. Cytotoxicity was detected using alamarBlue on days 1, 3, 5, and 7.

[0077] 3) If Figure 6 As shown in the figure, pure magnesium film has obvious cytotoxicity, while HA sample coating can alleviate this toxicity to a certain extent. In contrast, HAQ, HAGa and HAGaQ sample coating can significantly reduce the cytotoxicity of pure magnesium film and have a significant effect on promoting cell viability.

[0078] Embodiment 13

[0079] The samples obtained in the above examples 1-5 were subjected to ALP test, and the specific steps were as follows:

[0080] 1) Place the sample sterilized with 75% alcohol in a 5 mL centrifuge tube and add 1.6 mL of a-MEM complete medium; extract at 37°C for 72 hours to obtain a 100% extract.

[0081] 2) 1 mL was inoculated into each well of a 48-well plate at a density of 5×10 3 cell / mL of rat bone marrow mesenchymal stem cells.

[0082] 3) Place the cell culture plate in a 37°C, 5% CO 2 , incubate in a cell culture incubator with saturated humidity; replace 50% of the extract after 1 day of culture.

[0083] 4) The medium was changed every 3 days. After 7 days of culture, the alkaline phosphatase activity of the stem cells was detected using an alkaline phosphatase kit.

[0084] like Figure 7 As shown in the figure, compared with pure magnesium film, the surface ALP activity of HA, HAQ, HAGa and HAGaQ samples was significantly improved, among which HAGaQ sample performed best in promoting ALP expression activity.

[0085] Embodiment 14

[0086] The samples obtained in the above examples 1-5 were subjected to antibacterial plate testing under PBS environment, and the method was as follows:

[0087] 1) Place the sample sterilized with 75% alcohol into a 24-well culture plate and drip 0.5 mL of 10% 7 cfu / mL bacterial solution, incubated at 37°C for 16 hours;

[0088] 2) Transfer the sample to a 5 mL centrifuge tube, add 4 mL of PBS solution, and shake vigorously on an oscillator for 60 seconds to shake off the bacteria on the surface of the sample;

[0089] 3) Dilute the bacterial solution 1000 times with PBS solution, take 100 μL of the diluted bacterial solution and evenly spread it on TSB agar plate and continue to culture for 16 hours;

[0090] 4) Use a mobile phone to take a photo of the agar plate, count the colonies on the agar plate, and calculate the antibacterial rate of the sample.

[0091] like Figure 8As shown in the figure, the antibacterial rates of HA, HAQ, and HAGa samples are between 40% and 70%, while the antibacterial rates of HAGaQ samples and pure magnesium film are close to 100%. This shows that the HAGaQ sample not only performs well in corrosion resistance, but also has excellent antibacterial properties.

[0092] Embodiment 15

[0093] The samples obtained in the above Examples 1, 2, and 5 were subjected to in vivo antibacterial plate testing in the following manner:

[0094] 1) Place the sample sterilized with 75% alcohol under the skin of SD rats, and drip 20 μL of 10% 7 cfu / mL bacterial solution;

[0095] 2) The rats were killed 1 day and 4 days after the sample implantation, and the samples were taken out and placed in a 5 mL centrifuge tube containing 4 mL PBS solution. The tubes were shaken on an oscillator for 60 seconds to disperse the bacteria adhered to the surface into the solution, and 100 μL of the solution was taken to coat the plate.

[0096] 3) After 16 hours of incubation, take photos with a mobile phone, count and calculate the antibacterial rate.

[0097] 4) Obtain skin tissue in direct contact with the sample for paraffin embedding and sectioning, and use Giemsa staining to characterize the antibacterial effect of the sample.

[0098] like Fig. 9 As shown in the figure, the pure magnesium film cannot form a strong alkaline condition in the body due to its buffering effect, so it does not have antibacterial properties. In contrast, the HA sample prepared on the basis of the pure magnesium film showed a certain antibacterial ability. Furthermore, the HAGaQ sample showed the best antibacterial performance, and its antibacterial rate in the body reached almost 100%.

[0099] The present invention focuses on several key factors after GBR membrane implantation: the degree of inflammatory response, antibacterial effect, and the integration of soft and hard tissues, all of which are closely related to the surface properties of the membrane material. Modifying the surface of the material can enable it to obtain a more excellent tissue repair ability without destroying the properties of the matrix itself. The present invention proposes an innovative preparation method, that is, using a simple hydrothermal method to construct a nano-scale hydroxyapatite coating or a nano-scale hydroxyapatite composite coating on the surface of a magnesium-based metal. This method directly forms a nano-scale hydroxyapatite coating or a hydroxyapatite composite coating on a magnesium metal substrate under high temperature and high pressure conditions, and has significant high efficiency and excellent coating-substrate bonding strength. When creating a hydroxyapatite composite coating in situ, when the metal magnesium surface is hydrothermally treated, the high temperature and high pressure alkaline environment created causes hydroxyapatite and metal polyphenol particles to be deposited on its surface at the same time, and gradually merge into a dense composite coating. More importantly, this in situ generated coating exhibits better bonding strength due to its close bonding with the substrate material, and can be well applied in the preparation of guided bone regeneration membranes aimed at promoting osteogenesis in bone augmentation surgery.

[0100] The formation mechanism of the nano-hydroxyapatite composite gallium polyphenol coating in the present invention is as follows: on the one hand, the hydrothermal environment creates ideal conditions for the formation of the coating, including high temperature, high pressure and strong alkalinity, etc. These conditions are conducive to the deposition of calcium ions and phosphate ions on the surface of the magnesium-based metal, thereby forming hydroxyapatite particles. On the other hand, quercetin, as a catechol organic matter, can coordinate with gallium ions and magnesium ions in an alkaline environment to form metal polyphenol particles. These two components work synergistically under hydrothermal conditions, and finally form a uniform and dense nano-hydroxyapatite composite gallium polyphenol coating on the surface of the magnesium-based metal.

[0101] The EIS impedance value of the millimeter hydroxyapatite composite gallium polyphenol coating prepared by the present invention is 1.5×10 5 Ω, better than pure magnesium 3×10 2 Ω; The nano-hydroxyapatite composite gallium-polyphenol coating can stably release appropriate concentrations of quercetin, magnesium ions and gallium ions to promote the adhesion and proliferation of osteoblasts, and can also promote the proliferation of umbilical vein endothelial cells on the surface; the extract of the nano-hydroxyapatite composite gallium-polyphenol coating can promote the migration of umbilical vein endothelial cells; the hydroxyapatite in the nano-hydroxyapatite composite gallium-polyphenol particle coating has good biocompatibility and can promote the adhesion and proliferation of bone marrow mesenchymal stem cells on the surface; the nano-hydroxyapatite composite gallium-polyphenol coating shows excellent osteogenic differentiation ability; in the culture environment containing 50% of the coating extract, the alkaline phosphatase expression level of bone marrow mesenchymal stem cells was significantly better than that of the pure magnesium group; the nano-hydroxyapatite composite gallium-polyphenol coating showed long-lasting antibacterial properties both in vivo and in vitro environments.

Claims

1. A medical magnesium-based guided bone regeneration membrane, characterized in that: The invention comprises a pure magnesium substrate and a nanometer-scale hydroxyapatite coating or a nanometer-scale hydroxyapatite composite coating in-situ generated on the surface of the pure magnesium substrate.

2. The medical magnesium-based guided bone regeneration membrane according to claim 1, characterized in that: The nano-scale hydroxyapatite composite coating is a nano-hydroxyapatite composite quercetin coating, a nano-hydroxyapatite composite gallium ion coating or a nano-hydroxyapatite composite gallium polyphenol coating.

3. A method for preparing the medical magnesium-based guided bone regeneration membrane according to claim 1 or 2, characterized in that: The following steps are involved: (1) pre-treating the magnesium ingot into a pure magnesium square sheet as a pure magnesium matrix, and performing a grinding process; (2) A hydrothermal method is used to in situ construct a nano-hydroxyapatite coating, a nano-hydroxyapatite composite quercetin coating, a nano-hydroxyapatite composite gallium ion coating or a nano-hydroxyapatite composite gallium polyphenol coating on the surface of a pure magnesium substrate.

4. The method for preparing the medical magnesium-based guided bone regeneration membrane according to claim 3, characterized in that: The step (1) is to grind a pure magnesium ingot of 10 mm×10 mm×0.2 mm in size using 400 mesh and 1000 mesh silicon carbide sandpaper in turn, and then use alcohol ultrasonic cleaning twice, each time for 3-10 minutes to obtain a pure magnesium matrix, which is then stored in alcohol and taken out and dried before use.

5. The method for preparing the medical magnesium-based guided bone regeneration membrane according to claim 3, characterized in that: In the step (2), the nano-hydroxyapatite coating is constructed in situ by placing the pure magnesium substrate treated in the step (1) in a hydrothermal reactor containing a tetrafluoroethylene liner, adding a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at a pH of 9, and placing the substrate in an oven at 80-100° C. for treatment for 20-28 hours.

6. The method for preparing the medical magnesium-based guided bone regeneration membrane according to claim 3, characterized in that: The step (2) of in-situ construction of the nano-hydroxyapatite composite quercetin coating is to place the magnesium sheet treated in the step (1) in a hydrothermal kettle containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at a pH of 9, add 0.4-0.6g / L quercetin, and place in an oven at 80-100°C for treatment for 20-28h.

7. The method for preparing the medical magnesium-based guided bone regeneration membrane according to claim 3, characterized in that: The step (2) of in-situ constructing the nano-hydroxyapatite composite gallium ion coating is to place the magnesium sheet treated in the step (1) in a hydrothermal kettle containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at a pH of 9, add 0.8-1.2g / L gallium nitrate, and place in an oven at 80-100°C for treatment for 20-28h.

8. The method for preparing the medical magnesium-based guided bone regeneration membrane according to claim 3, characterized in that: The step (2) of in-situ constructing the nano-hydroxyapatite composite gallium polyphenol coating is to place the magnesium sheet treated in the step (1) in a hydrothermal kettle containing a tetrafluoroethylene liner, add a precursor solution containing 0.05M calcium ethylenediaminetetraacetate and 0.05M potassium dihydrogen phosphate at a pH of 9, add 0.4-0.6g / L quercetin and 0.8-1.2g / L gallium nitrate, and place in an oven at 80-100°C for treatment for 20-28h.

9. A medical magnesium-based guided bone regeneration membrane as claimed in claim 1 or 2, characterized in that: Application in the preparation of guided bone regeneration membrane aimed at promoting osteogenesis in bone augmentation surgery.